2020
DOI: 10.1097/prs.0000000000006373
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Knowledge Gap: An Examination of the Ideal Postoperative Autologous Breast Reconstruction Educational Material with A/B Testing

Abstract: Background: Poor health literacy is an epidemic in the United States, associated with higher mortality rates and poor postoperative care. Autologous breast reconstruction is highly complex, and the identification of complications is difficult even for non–plastic surgeon practitioners. The authors sought to explore the problem of health literacy in this context and identify the ideal postoperative patient education materials. Methods: Available online p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Forty-five articles were ultimately included for data extraction (Table 1). 13–57 Proportionate rater agreement was 91.7% for abstract screening and 92.5% for full-text screening. The Cohen kappa coefficient for interrater reliability was 0.82 for abstract screening and 0.81 for full-text screening, demonstrating sufficient interrater reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five articles were ultimately included for data extraction (Table 1). 13–57 Proportionate rater agreement was 91.7% for abstract screening and 92.5% for full-text screening. The Cohen kappa coefficient for interrater reliability was 0.82 for abstract screening and 0.81 for full-text screening, demonstrating sufficient interrater reliability.…”
Section: Resultsmentioning
confidence: 99%
“…After incorporating participants' feedback into the finalized material, the readability of the material is at the recommended reading level. The material also had the recommended length (between 400 and 800 words) 23 …”
Section: Discussionmentioning
confidence: 99%
“…The material also had the recommended length (between 400 and 800 words). 23 After investigating the breast-related patient education materials provided by local hospitals, plastic surgery societies, and federal agencies, we found that none of the materials were considered easy to comprehend. This is similar to the findings of Powell et al, 9 which concluded that the readability of breast reconstruction patient education materials from major US academic hospitals is much higher than the recommended reading level.…”
Section: Discussionmentioning
confidence: 99%
“…Although research on HL in oculofacial plastic surgery is sparse, multiple studies propose solutions to improve the quality of patient-surgeon communication and address HL in plastic surgery [13,45,46]. There should be an effort to incorporate tools that have proven effective in other surgical specialties into the field of oculofacial plastic surgery [45,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%